The Effect of Financial Literacy, Overconfidence, and Herding Behavior on Application-Based Investment Decisions - Zima, Zahrul; Dharma, Fitra; Susilowati, Retno Yuni Nur (Goodwood Akuntansi dan Auditing Reviu, 2025)
Purpose: This study examines the influence of financial literacy, overconfidence, and herding behavior on investment decisions made through digital-based applications. It aims to determine which cognitive and behavioral factors most significantly shape investors’ decision-making in the digital era. Methodology: The research applies a quantitative approach using a survey method involving 400 individual investors in Sumatra, Indonesia, selected through purposive sampling. Data were collected via an online questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The analysis covered the outer model (validity and reliability) and the inner model (path coefficients and significance testing). Results/findings: The results indicate that financial literacy, overconfidence, and herding behavior each have a positive and significant effect on application-based investment decisions. These findings show that knowledge, self-confidence, and social influence play vital roles in shaping investors’ behavior in digital investment platforms. Conclusions: Investors’ decisions in digital applications are influenced by both cognitive and social psychological factors, supporting behavioral finance theory, which asserts that investment behavior is not entirely rational. Limitations: This study is limited to individual investors in Sumatra and uses self-reported data, which may cause response bias. It also excludes external factors such as market volatility, emotional regulation, and platform usability that could affect investment behavior. Contribution: This research enriches behavioral finance literature by examining financial literacy, overconfidence, and herding behavior together in the context of digital investment platforms in Indonesia, offering new empirical evidence on their combined influence on investment decisions.